A new gigantic titanosaurian sauropod from the early Late Cretaceous of Patagonia (Neuquén Province, Argentina) - Simón, María Edith (2023)
A new gigantic titanosaur Bustingorrytitan shiva gen. et sp. nov. is described. The four specimens upon which this species is erected come from Neuquén Province, Argentina, from levels of the Huincul Formation (Cenomanian). Bustingorrytitan shiva gen. et sp. nov. exhibits some autapomorphic characters such as posterior dorsal vertebrae with spinodiapophyseal laminae bifurcated in two, very well developed anterior and posterior spinodiapophyseal lamina rami, which limit a deep, vertical, socket-like fossa; posterior dorsal neural arches with forked centropostzygapophyseal laminae; hyposphene in anterior caudal vertebrae; humerus with deltopectoral crest strongly expanded distally; and femur with a low longitudinal crest on the lateromedial half of the anterior face, bifurcated in two minor crests, which are directed to their respective condyles. The phylogenetic analysis performed recovers B. shiva gen. et sp. nov. as a lithostrotian, the sister taxon of Saltasauridae. The estimated body mass is 67.297 metric tons (with a standard error of ±17.228), which makes B. shiva gen. et sp. nov. one of the largest sauropods ever recorded. The record of this new sauropod corroborates the idea that gigantism (evolution of forms over the 50 metric tons) would have evolved many times within Eutitanosauria.